Pembelajaran IPS dan Regulasi diri: Internalisasi Nilai Sosial untuk Harmoni keberagaman di SMP Singkawang - Toni Toni; Agustinus Sugeng Priyanto (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Nowadays, self-regulation is very important in shaping students' character. With self-regulation skills, students become sensitive to everything in their environment. However, in reality, self-regulation is not widely practiced by students, especially in a multicultural society where students are expected to be sensitive to their surroundings in order to minimize conflicts between ethnic groups, classes, and religions. This study aims to analyze the role of Social Studies (IPS) education and self-regulation in developing social values to achieve harmony at SMP Negeri 1 Singkawang, as well as its implications for social and cultural resilience. Using a qualitative phenomenological approach, data was collected through in-depth interviews, participatory observation, and documentation, and then analyzed thematically. The findings indicate that the integration of SSE learning emphasizing understanding diversity, combined with the development of students' self-regulation, significantly contributes to strengthening social values such as tolerance, empathy, and mutual respect. These findings are important for strengthening the nation's social and cultural resilience through contextual education, especially in diverse regions like Singkawang. This research is expected to serve as a foundation for developing a more inclusive and holistic social studies curriculum, as well as learning strategies that promote students' self-regulation as a foundation for living in a diverse society.